Implementation of Literacy Culture in Improving the Character of Students: Case Study at SMA Asshiddiqiyah Garut - Munawaroh, Nenden; Nazib, Fiqra Muhamad; Putri, Megawati (Al-Abshar: Journal of Islamic Education Management, 2022)
Character issues always color human life from time to time, along with the times and the development of the world of education, efforts are made to achieve good character. In the world of education, literacy activities are a place for character building. For this reason, the character has an important role in Islam and cannot even be separated from human life. This study aims to find out how the description of literacy and character-building activities for students at SMA Asshiddiqiyah Garut, so that the results can be known. This research was conducted using quantitative research with survey analysis techniques, namely research that was taken based on the phenomena that occurred by making decisions from the sample data using statistical tests. From the results of the study, it is known that based on the results of testing on 35 students, it is known that literacy culture has a positive effect on the formation of students' character where the t count value 5.745 the t table 2.011. While the value of the coefficient of determination is 58.21% which shows the large contribution of the influence. And the remaining 41.79% is influenced by other variables not examined. Thus, this study states that the implementation of a literacy culture can improve the character of students.